“I feel good with my teachers”. The effects of positive teacher-student relationship on students’ self-esteem and perceptions about their future. - Marini, Mara; Livi, Stefano; Cecalupo, Alessandra; Scarci, Federica; Santini, Francesca; Parisse, Chiara; Benvenuto, Guido (Psychology Hub, 2023)
The school climate has long been acknowledged as a protective factor for children’s and adolescents’ well-being. In fact, research has demonstrated that learning environments based on positive relationships among various social actors (students, teachers, and parents) are essential for enhancing students’ global self-evaluations and fostering their positive adaptation. However, few studies have examined the role teachers’ play in students’ self-esteem and future expectations. To overcome this limitation present in the literature, particularly in the Italian context, this study investigated the effect of teachers-students relationship on students’ self-esteem and their expectations for the future. The study employed a sample of 287 high school students. The mediational models included the quality of the teachers-students relationship as the independent variable, students’ self-esteem as the mediating variable, and students’ future expectations as the dependent variable. The results indicated total mediation: positive relationships between teachers and students had a positive association with students’ self-esteem which, in turn, had a positive association with students’ future expectations. The study emphasizes that socio-relational competencies are an essential component of teachers’ professionalism and are linked to the well-being of their students.